IMMUNE PREVENTION OF RESPIRATORY-SYNCYTIAL VIRAL INFECTION: 15 YEARS OF WORLD EXPERIENCE - E. S. Keshishyan (Union of pediatricians of Russia, 2013)
The article is dedicated to one of the most important issues of modern neonatology - prevention of respiratory-syncytial virus infection, which is a frequent cause of bronchiolites and pneumoniae in infants and neonates, especially premature infants. The latter belong to the high-risk group for the development of this infection with unfavorable outcome. The authors present detailed data on epidemiology and world spread of respiratory-syncytial virus infection, its consequences (short-term and long-term) and prevention possibilities. The authors demonstrate efficacy of passive palivizumab (humanized monoclonal antibody) immune prevention on the basis of multiple studies conducted in different countries. The authors show the process of formation of national recommendations for immune prevention of development of this infection. Apart from the main risk groups for the development of respiratory-syncytial virus infection, acknowledged by the scientists, the authors also present additional groups - children with mucoviscidosis, Down's syndrome, neuromuscular diseases and immune compromised patients due to the primary immune deficiency or in the setting of immune suppressive therapy.